Principles Of economics - Mankiw, N. Gregory (Cengage Learning Asia, 2013)
The book reflects Asian economic institutions and policy, features companies that operate in the region, and includes economic data from various Asian countries. Written for students taking economics for the first time, the book focuses on the core concepts and how these concepts are applied to the real world.